The Influence of Privacy and Trust on the Adoption of Internet Banking in Bangladesh (Malaysian Management Journal, 2010)
In Bangladesh, the expansion of Internet banking is beset with several infrastructural, institutional, and regulatory constraints. Despite the constraints, efforts by the Bangladesh Bank in modernizing the country’s payment system and commitment by the government in building ‘Digital Bangladesh’ have brought competition among the scheduled banks to improve banking services and rapidly adopt Internet banking on a wider scale. However, several opinion polls have revealed that many clients are found reluctant in adopting banking via the Internet because of their concerns about the privacy of the personal information they provide to online. Using the theory of planned behaviour as its theoretical basis, this study examined the relationships among beliefs about Internet privacy and trust, along with beliefs about perceived behavioural control and the expectations of important others and online banking behaviour. Data were collected from 327 university students. Analysis of the data indicates that beliefs about trust and privacy positively affect attitudes toward Internet banking, but attitude is found not to significantly affect Internet banking behaviour. Normative beliefs positively affect subjective norms which in turn affect Internet banking behaviour. Similarly, beliefs about self-efficacy regarding Internet banking positively affect perceived behavioural control, which in turn affects actual online banking behaviour.